5-Arylpyrimido-[4, 5-b]quinoline-diones as new and sustainable corrosion inhibitors for mild steel in 1 M HCl: a combined experimental and theoretical approach. Issue 19 (8th February 2016) - Verma, Chandrabhan; Olasunkanmi, L. O.; Obot, I. B.; Ebenso, Eno E.; Quraishi, M. A.
Abstract : The inhibition of mild steel corrosion in 1 M HCl by four 5-arylpyrimido-[4, 5- b ]-quinoline-diones has been investigated using weight loss, electrochemical, surface, and quantum chemical calculations and molecular dynamics simulation methods. Abstract : The inhibition of mild steel corrosion in 1 M HCl by four 5-arylpyrimido-[4, 5- b ]quinoline-diones (APQDs), namely 5-(4-nitrophenyl)-5, 10-dihydropyrimido [4, 5- b ]quinoline-2, 4(1 H, 3 H )-dione (APQD-1 ), 5-phenyl-5, 10-dihydropyrimido[4, 5- b ]quinoline-2, 4(1 H, 3 H )-dione (APQD-2 ), 5-(4-hydroxyphenyl)-5, 10-dihydropyrimido[4, 5- b ]quinoline-2, 4(1 H, 3 H )-dione (APQD-3 ) and 5-(2, 4-dihydroxyphenyl)-5, 10-dihydropyrimido[4, 5- b ]quinoline-2, 4(1 H, 3 H )-dione (APQD-4 ) has been investigated using weight loss, electrochemical, surface, and quantum chemical calculations and molecular dynamics simulation methods. The results showed that the inhibition efficiency ( η %) increased with increasing concentration of the inhibitors. Among the studied compounds, APQD-4 exhibited the highest inhibition efficiency of 98.30% at 20 mg l −1 concentration. The studied compounds effectively retarded the corrosion of mild steel in 1 M HCl by adsorbing onto the steel surface, and the adsorption data conformed to the Langmuir adsorption isotherm. The results of potentiodynamic polarization measurements revealed that the studied compounds are cathodic-type inhibitors. Scanning electron microscopy (SEM) study confirmed the formation of adsorbed films of the inhibitor molecules on the steel surface. Quantum chemical calculations and molecular dynamics simulations were undertaken to corroborate experimental findings and provide adequate insight into the corrosion inhibition mechanisms and adsorption characteristics of the studied compounds.